2009
DOI: 10.1093/bja/aen381
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an increased intracranial pressure on cerebral and systemic haemodynamics during endoscopic neurosurgery: an animal model

Abstract: Upon complete suppression of the CPP, an obvious hypertension developed, often together with tachycardia, but no severe bradycardia. At high ICP levels, we observed an important translocation of irrigation fluid to the vascular space. Fatality was not caused by ischaemia or arrhythmia but due to pulmonary oedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Tachycardia has been demonstrated in response to raised intracranial pressure in a number of neurosurgical procedures, and the bradycardia of Cushing's triad is known to be a late-stage phenomenon (Kalmar et al 2009). However, a tachycardic response and compensatory hypertension appears unlikely after such a localised infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Tachycardia has been demonstrated in response to raised intracranial pressure in a number of neurosurgical procedures, and the bradycardia of Cushing's triad is known to be a late-stage phenomenon (Kalmar et al 2009). However, a tachycardic response and compensatory hypertension appears unlikely after such a localised infusion.…”
Section: Discussionmentioning
confidence: 99%
“…The principal reasons for induced intracranial hypertension are high flow rinsing (used to improve visibility during bleeding or to maintain access in collapsing ventricles ) and obstruction of the outflow channel by tissue debris , blood clots or kinking of outflow tubes. These increases in ICP must be detected as soon as possible to prevent severe complications such as cardiovascular instability (Fabregas et al, 2002, Handler et al, 1994 , herniation syndromes, retinal bleeding (Boogaarts et al, 2008 ;Hoving et al, 2009) and excessive fluid resorption (Kalmar et al, 2009). Aside from these unambiguous complications animal research showed that awakening without apparent neurological deficit does not preclude histological damage (Kalmar et al 2009).…”
Section: Intraoperative Monitoringmentioning
confidence: 99%
“…It is very conceivable that the differences in these observations are a result of variations in surgical practice. Additionally, direct pressure on certain anatomical regions seems mainly to provoke bradycardia (Baykan et al, 2005), while isolated intracranial hypertension seems rather to induce tachycardia (Kalmar et al, 2009). Al-Dawlatly suggests that the possible absence of tachycardia found in many studies may be due to the protocol that allows the irrigation fluid to vent out during the procedure without noticeable accumulation in the third ventricle.…”
Section: Intracranial Pressure and The Cushing Reflexmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive increases in ICP should be avoided, since intracranial hypertension can lead to cardiovascular complications, 11 12 herniation syndromes, retinal bleeding, 8 10 and excessive fluid resorption. 13 Transcranial Doppler ultrasonography measurements during rinsing procedures have shown severe decreases in cerebral perfusion without systemic haemodynamic warning signs. 14 ICP monitoring is thus important, but the optimal location of monitoring is controversial.…”
mentioning
confidence: 99%